2010
DOI: 10.1002/eji.201040340
|View full text |Cite
|
Sign up to set email alerts
|

HCV‐specific T cells in HCV/HIV co‐infection show elevated frequencies of dual Tim‐3/PD‐1 expression that correlate with liver disease progression

Abstract: Co-infection of HCV with HIV has been associated with more rapid progression of HCV-related disease. HCV-specific T-cell immune responses, which are essential for disease control, are attenuated in co-infection with HIV. T-cell exhaustion has recently been implicated in the deficient control of chronic viral infections. In the current study, we investigated the role of programmed death-1 (PD-1) and T-cell immunoglobulin and mucin domain-containing molecule-3 (Tim-3) expression in T-cell exhaustion during HCV/H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
88
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 34 publications
5
88
1
Order By: Relevance
“…Increased frequency of Tim-3 + T cells is reported in tuberculosis (8). We and other investigators subsequently showed that the chronic virus infections HIV-1 (9) and hepatitis C virus (10,11) are also associated with upregulation of Tim-3 on T cells. In addition, elevated expression of Tim-3 on virus-specific T cells correlated with increased viral load and disease progression (8)(9)(10)(11).…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Increased frequency of Tim-3 + T cells is reported in tuberculosis (8). We and other investigators subsequently showed that the chronic virus infections HIV-1 (9) and hepatitis C virus (10,11) are also associated with upregulation of Tim-3 on T cells. In addition, elevated expression of Tim-3 on virus-specific T cells correlated with increased viral load and disease progression (8)(9)(10)(11).…”
mentioning
confidence: 66%
“…We and other investigators subsequently showed that the chronic virus infections HIV-1 (9) and hepatitis C virus (10,11) are also associated with upregulation of Tim-3 on T cells. In addition, elevated expression of Tim-3 on virus-specific T cells correlated with increased viral load and disease progression (8)(9)(10)(11). Subsequent studies showed that Tim-3 expression is also upregulated on tumor-infiltrating T cells, thus providing an additional mechanism of tumor escape from the immune response (12).…”
mentioning
confidence: 74%
“…The amount of viral Ag produced in the latently infected TG of mice following UV-B reactivation is quite low, less than 1 positive neuron/TG (66)(67)(68)(69). Thus, it is likely that the CXCL10/CXCR3 chemokine pathway inhibits exhaustion of CD8 ϩ T cells in TG through mechanisms other than Ag persistence, as we previously discussed (70).…”
Section: Discussionmentioning
confidence: 90%
“…Antibodies targeting the PD-1/PD-L1 (programmed death ligand 1) immune checkpoint have recently shown remarkable clinical safety and efficacy in other systems (76)(77)(78). The current largely accepted paradigm is that exhaustion of T cells requires persistent exposure to Ag (66)(67)(68)(69). Elucidating the mechanisms by which the CXCL10/CXCR3 pathway might be preventing CD8 ϩ T cell exhaustion remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…This issue is of particular concern because the prevalence of HCV infection among HIV-positive persons is high (24%) and, conversely, 81% of HIV-positive persons with a history of IDU are anti-HCV-positive [13]. HIV-HCV-coinfected persons are at a greater risk of progressing to an AIDS-defining event or death than those who are HIV monoinfected [29], and progress to end-stage liver disease in less than half the time of HCV-monoinfected persons [30,31].…”
Section: Discussionmentioning
confidence: 99%